Analysis of Value Added Tax Treatment Based on Law No.7 of 2021 at PT. YJG - Hanan, Muhammad Syaepul; Hambani, Susy; Aziz, Ayi Jamaludin (Institut Bisnis dan Informatika Kesatuan, 2024)
Tax is a government levy based on law that is used to finance state needs and improve the welfare of the people. Value Added Tax (VAT) is one of the main sources of state revenue, imposed on the consumption of Taxable Goods both within and outside the customs area. VAT also serves as a community contribution to support development funding across various sectors. This study aims to analyze the application of VAT based on Law No. 7 of 2021 at PT YJG. The study employs a descriptive method, involving the collection and comparison of actual data with theoretical frameworks, leading to an analysis related to the calculation, payment, and reporting of the company's VAT. The focus is on the calculation of input tax, output tax, and VAT reporting in compliance with the provisions of Law No. 7 of 2021, Chapter IV, Article 1. The results indicate that the VAT treatment at PT YJG adheres to the applicable provisions, including the implementation of an 11% VAT rate. Additionally, an analysis of the company's profit and loss report was conducted to assess the impact of the VAT calculation compared to the legal provisions. In conclusion, PT YJG fulfills its tax obligations in accordance with the prevailing regulations.